PENGARUH PENGGUNAAN METODE ROLE PLAYING TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL PADA ANAK SEKOLAH - Miftahul Hayatun; Nurhasanah Nurhasanah; Siti Istiningsih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2020)
During the learning process, it was found that students did not treat their friends kindly; they did not answer questions from friends and teachers seriously. Moreover, the studets were also less motivated in learning and did not keep the learning atmosphere conducive. These were caused by the difference of the students' social-emotional development. Thus, teachers needed to find a method to foster the students' social-emotional development; one of which was role-playing method. The purpose of this study was to find the effect of role-playing method on the students' social-emotional development at grade III group 2 Ambalawi in the academic year 2020/2021. The design of this study was Non-equivalent Control Group Design. Then, the population of this study was all grade III elementary school students of group 2 Ambalawi in the academic year 2020/2021. The samples were selected by purposive sampling and the students of grade III SDN 1 Rite were as the experimental class and the students of grade III SDN Inpres 2 Rite were as the control class. After  that, the hypotheses were tested by the formula of independent sample t-test and the data were analyzed by using SPSS version 16.0. the results of data analysis showed that the value of t-count was 9,917 and t-table was 2,042 meaning that t-count ≥ t-table. By looking at the Sig. (2-tailed) 0,000 ≤ 0.05, the significant level of 5% with df 30, it was revealed that Ha was accepted. This implied that role-playing method provided significant influence on the students' social-emotional development at grade III group 2 Ambalawi in the academic year 2020/2021.